CERVICAL CANCER IN WOMEN OVER 76 YEARS. COMPARISON WITH PATIENTS UNDER 25 YEARS - Castellano Soule, Carlos (2015)
Of the 17.326 patients with cervical cancer registered in the INEN between 1952 and 1979, 403 were 76 years or older at diagnosis (2.3%). The average age in this group was 80.6 years and older was 99 years. The first sex was at 19 and the average latency period 61 years, in contrast to 16 and seven years for the group of 123 patients under 25 years. The distribution showed predominance of clinical stay in the añosas advanced disease, although the parametrial involvement (comparison between stays A and B) was significantly lower (p <0.001) than in young, possibly due to anatomical changes involution. Squamous cell carcinoma was the predominant type and significantly more frequent (98%) in those over 76, with lower incidence of adenocarcinoma and mucoepidermoid carcinoma. The linioplasmocitario cervical stromal infiltrate was more frequent in younger patients, in which an inverse relationship between this reaction and the extent of the disease warned. The absence of these features in añosas patients could be interpreted as a decrease in responsiveness to neoplastic aggression.